Computed tomography evaluation of root canal transportation using ProTaper, Race and Sendoline rotary systems: an ex vivo study - Saberi E; Aramesh B (Dove Medical Press, 2018)
Eshaghali Saberi,1 Bita Aramesh2 1Department of Endodontics, Oral and Dental Disease Research Center, Dental School, Zahedan University of Medical Sciences, 2Department of Endodontics, Dental School, Zahedan University of Medical Sciences, Zahedan, Iran Background: This ex vivo study aimed to compare transportation of the mesiobuccal root canal of mandibular first molars instrumented with ProTaper, Race and Sendoline rotary systems using cone beam computed tomography (CBCT). Materials and methods: Forty-five mesiobuccal canals of mandibular first molars were randomly divided into three groups of 15. Root canals in each group were instrumented with the ProTaper, Race or Sendoline rotary system according to the manufacturers’ instructions. Root canal preparations were performed by one operator, while root canal wall measurements were made by another operator blinded to the group allocation of teeth. The pre- and post-chemomechanical preparation CBCT scans were obtained and evaluated at 3, 6 and 9 mm levels from the apex. The amount of root canal transportation at these levels was calculated. Data were analyzed using SPSS version 17 via Mann–Whitney and Kruskal–Wallis tests. P<0.05 was considered significant. Results: No significant difference was noted in canal transportation among the groups (P>0.05), but ProTaper showed the least and Sendoline caused the most canal transportation in the coronal third. Conclusion: ProTaper, Race and Sendoline rotary systems are not significantly different in terms of canal transportation. Although all rotary files cause root canal transportation, ProTaper and Race showed the least amount of canal transportation in the coronal and apical thirds, respectively. Keywords: canal transportation, ProTaper, Race, Sendoline, rotary systems, cone beam computed tomography